Tryptanthrin promotes keratinocyte and fibroblast responses in vitro after infection with Trichophyton benhamiae DSM6916 - Hesse-Macabata, Jana (Sci Rep, 2020)
Exceedingly virulent pathogens and growing antimicrobial resistances require new therapeutic approaches. The zoophilic dermatophyte Trichophyton benhamiae causes highly inflammatory, cutaneous fungal infections. Recently, it could be shown that the plant-derived alkaloid tryptanthrin (TRP) exhibits strong anti-microbial activities against yeasts and dermatophytes. The aim of this study was to analyse the bioactivity of TRP under infectious conditions using an in-vitro dermatophytosis model employing fibroblasts and keratinocytes infected with T. benhamiae DSM6916. Analyses comprised determination of cell viability, effects on the innate immune response including expression and secretion of pro-inflammatory cytokines/chemokines as well as expression of various antimicrobial peptides (AMP), toll-like receptor (TLR) 2 and proliferation marker MKI67. T. benhamiae caused severe inflammation in the cutaneous cell models. TRP almost fully prevented T. benhamiae-derived damage of dermal fibroblasts and substantially reduced it in epidermal keratinocytes. A distinct down-regulation of the expression and secretion of pro-inflammatory cytokines was observed. Further, TRP promoted AMP expression, especially of HBD2 and HBD3, in keratinocytes even without fungal presence. This study provides crucial evidence that TRP is not only a strong antifungal agent but also potentially modulates the innate immune response. This makes it interesting as a natural antimycotic drug for adjuvant treatment and prevention of fungal re-infection.